High‐Fat‐Diet Intake Enhances Cerebral Amyloid Angiopathy and Cognitive Impairment in a Mouse Model of Alzheimer's Disease, Independently of Metabolic Disorders. Issue 6 (13th June 2016) - Lin, Bowen; Hasegawa, Yu; Takane, Koki; Koibuchi, Nobutaka; Cao, Cheng; Kim‐Mitsuyama, Shokei
Abstract : Background: The high‐fat Western diet is postulated to be associated with the onset and progression of Alzheimer's disease (AD). However, the role of high‐fat‐diet consumption in AD pathology is unknown. This study was undertaken to examine the role of high‐fat‐diet intake in AD. Methods and Results: 5XFAD mice, a useful mouse model of AD, and control wild‐type mice were fed (1) high‐fat diet or (2) control diet for 10 weeks. The effects on cerebral AD pathology, cognitive function, and metabolic parameters were compared between each group of mice. High‐fat diet significantly enhanced cerebrovascular β‐amyloid (Aβ) deposition ( P <0.05) and impaired cognitive function ( P <0.05) in 5XFAD mice, but not in wild‐type mice. High‐fat diet enhanced hippocampal oxidative stress ( P <0.05) and NADPH oxidase subunits, gp91 phox ( P <0.01) and p22 phox ( P <0.01) in 5XFAD mice, but not in wild‐type mice. Furthermore, high‐fat diet reduced cerebral occludin ( P <0.05) in 5XFAD mice, but not in wild‐type mice. Thus, 5XFAD mice exhibited greater susceptibility to high‐fat diet than wild‐type mice regarding cerebrovascular injury and cognitive impairment. On the other hand, 5XFAD mice fed high‐fat diet exhibited much less increase in body weight, white adipose tissue weight, and adipocyte size than their wild‐type counterparts. High‐fat diet significantly impaired glucose tolerance in wild‐type mice but not in 5XFAD mice. Thus, 5XFAD mice had much less susceptibility to high‐fat‐diet‐induced metabolic disorders than wild‐type mice. Conclusions: High‐fat diet, independently of metabolic disorders, significantly promotes the progression of AD‐like pathology through enhancement of cerebral amyloid angiopathy and oxidative stress.